New species of Chironomus Meigen (Diptera: Chironomidae: Chironominae) from Brazil - Da Silva Correia, Leny Célia; Trivinho-Strixino, Susana (Zootaxa, 2007)
Five new species of Chironomus Meigen, C. detriticola, C. antonioi, C. phytophilus, C. oliveirai, and C. fittkaui, are described and figured as male, pupa, and larva. The species live in different water systems in São Paulo State, Southeastern Brazil.